FORMULATION AND EVALUATION OF CREAMS CONTAINING CELECOXIB INCLUSIONS FOR TREATING PSORIATIC ARTHRITIS - RANI N, ROOPA; B, SUDHARSHAN; REDDY G, SHIVA PULLA; IRIVENTI, PADMINI (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The main objective of the present work was to prepare and evaluate creams of celecoxib inclusions which are nonsteroidal anti-inflammatory drug to treat psoriatic arthritis. Methods: Celecoxib inclusions were prepared using β-cyclodextrin to increase the solubility. These inclusions were incorporated in creams. Cocoa butter, triethanolamine, stearic acid, methylparaben, gum acacia, and coconut oil were used in cream preparation. Fourier transform infrared and differential scanning calorimetry studies were carried out for pure celecoxib and inclusions. Viscosity, pH, homogeneity, and type of emulsion under dye test were evaluation parameters done for creams. Results: All the results obtained were within the limits and confirmed increased solubility of celecoxib inclusions. Conclusion: From the results obtained, increase in solubility of celecoxib drug was confirmed by forming inclusions using β-CD as polymer.